The Effect of Using Solid Tofu Waste and Banana Peel Waste as Liquid Organic Fertilizer with Different Volumes on the Growth and Production of Green Mustard Plants (Brassica juncea L.) - Fenesia Tokael; Yusnaeni; Mario Justinianus Santrum; Nikmah (Pendidikan MIPA Universitas Nusa Cendana, 2025)
The purpose of this study was to determine the effect of using liquid organic fertilizer made from tofu solid waste and banana peel waste on the growth and production of green mustard plants and to determine the dosage of liquid organic fertilizer that gives the best results for the growth and production of green mustard plants.This study is an experimental study using a completely randomized design consisting of 5 treatments, each repeated 5 times. The 5 treatments are liquid organic fertilizer made from tofu solid waste and banana peel waste, namely control/without POC 0 ml (P0), POC 50 ml (P1), POC 100 ml (P2), POC 200 ml (P3), and POC 400 ml (P4). The parameters observed were leaf width and plant fresh weight. The observation data were analyzed using an ANOVA test, followed by a post-hoc least significant difference (LSD) test.The results of the study indicate that the application of liquid organic fertilizer made from tofu solid waste and banana peel waste has a significant effect on the growth and production of green mustard plants, as evidenced by the ANOVA test results showing an Fcalculated value > Ftable value. The Fcalculated value for the leaf width parameter was 183.336 (> Ftable 1% = 4.43), and the Fcalculated value for the fresh weight parameter was 49.36707 (> Ftable 1% = 4.43). From the BNT followup test, the value obtained for the leaf width parameter was 0.77, and the BNT follow-up test result for the fresh weight parameter was 12.74.